Lactic acid bacteria in the gastrointestinal tract: Anti-helicobacter pylori - Techo, Sujitra; Kingkaew, Engkarat; Tanasupawat, Somboon (My University, 2024)
Numerous bacterial species have been found throughout the human GI tract, which consists of the oral cavity, stomach, intestine, and colon. Lactic acid bacteria (LAB), including Lactobacillus (L. ) acidophilus, L. salivarius, L. johnsonii, L. crispatus, L. casei, L. paracasei, L. rhamnosus, L. reuteri, L. oris, L. vaginalis, L. gasseri, L. plantarum, L. buchneri, L. mali, L. ruminis, L. delbrueckii, L. sakei, L. fermentum, L. helviticus, and L. brevis ; Streptococcus ( S. ) salivarius, S. pneumonia, S. mitis, S. oralis, S. parasanguinis, S. anginosus, S. constellatus, S. caprinus, and S. mutans ; Leuconostoc (Ln. ) mesenteroides and Ln. argentinum ; Lactococcus (Lc.) lactis; and Enterococcus (En. ) strains, are distributed throughout the human GI tract. The bacterial microbiota in humans changes when infected with Helicobacter (H. ) pylori. Moreover, antibiotics and proton pump inhibitors (PPIs) used in the regimen influence microbial microbiota. However, alteration of bacterial diversity is rather complicated and has conflicting effects. To maintain microbial balance in the GI tract, several studies have used probiotics as adjunctive therapy to reduce the number of H. pylori in infected humans, replacing antibiotics alone. Probiotics have shown a higher eradication rate of H. pylori when compared with antibiotics alone. Bacteriocin production by LAB is one of the interesting mechanisms that can inhibit the growth of H. pylori. Bacteriocins and bacteriocin-like substances exhibiting antibacterial properties against H. pylori have been reported. These active peptides could be exploited to develop novel therapeutics for treating H. pylori infection.
Keywords: Antibiotics; Bacteriocins; Gastrointestinal tract; Gut microbiota; Helicobacter pylori; Lactic acid bacteria; Probiotics